Estudio epidemiológico de leptospirosis en cuyes en las parroquias Chantaco y Chuquiribamba del cantón Loja - Carrión Montaño, Katherine Elizabeth (2022)
Leptospirosis is one of the most important zoonoses worldwide, being classified as an emerging disease; rodents are considered the main reservoir of the bacteria, favoring its transmission through the elimination of contaminated urine. In Ecuador, there are no investigations that allow knowing the epidemiology of leptospirosis in guinea pigs, for that reason, this study was carried out in areas of importance in the production of guinea pigs in Canton of Loja. The objectives were to determine the frequency and factors associated with leptospirosis in guinea pigs in the Chantaco and Chuquiribamba parishes by collecting information based on an epidemiological survey in the field and sampling 175 guinea pigs older than eight weeks in order to carry out the study serological analysis using the MAT (microscopic agglutination) test. The following results were obtained, the frequency of infection was estimated at 5.71%, seropositive animals were identified for six serovars: Pomona (1.71%), Hardjo (1.14%), Tarassovi (1.14%), Sejroe (0.57%), Betaviae (0.57%) and Canicola (0.57%); Regarding the associated factors, statistically significant values were obtained with the origin of the animals and the presence of (cats) and rodent control through chemical and biological methods. The results found in this research may serve as reference data to continue studying the epidemiology of the disease in this species in Ecuador, since they constitute relevant data for health authorities to develop strategies and lines of action that help control the disease. Keywords: Leptospirosis, MAT, Cavia porcellus, zoonoses, Ecuador.